The Effectiveness of The Culture-Based Anti-Stunting Education Package on Family Behavioral Changes in Stunting Prevention - Dwining Handayani Handayani; Erik Kusuma; Ayu Dewi Nastiti; R.A. Helda Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Stunting remains a pressing global health concern, as evidenced by the prevalence of stunting in Indonesia. The Pasuruan Regency Government continues its efforts to reduce the stunting rate. Coastal areas are characterized by a relatively high incidence of stunting, which stands at 22.8%. The urgency of this research lies in the need for a change in family behavior toward stunting prevention through education optimalization in coastal areas. Stunting prevention education within the family can be summarized into the